Macro-Prudential Regulation - Persaud, Avinash (World Bank, Washington, DC, 2012)
This is not the first international banking crisis the world has seen. The previous ones occurred without credit default swaps, special investment vehicles, or even credit ratings. If crises keep repeating themselves, it seems reasonable to argue that policy makers need to carefully consider what they are doing and not just 'double up' by superficially reacting to the specific features of today's crisis. While we cannot to prevent crises, we can perhaps make them fewer and milder by adopting and implementing better regulation in particular, more macro-prudential regulation.